NUMERICAL STUDY OF A CAPACITIVE TOMOGRAPHY SYSTEM FOR MULTIPHASE FLOW - Moura, L. F. M.; Cenedese, E.; Azevedo Filho, A. C. (Revista de Engenharia Térmica, 2009)
This paper presents the development of a capacitive tomography system applied to the study of multiphase flows. A numerical analysis, through the finite elements method, was performed to obtain data for the optimization of the geometry of the capacitance sensor. The image reconstruction of several flow patterns was obtained through the method of linear back projection, allowing the verification of the influence of several parameters upon the quality of the images, making its application easier in an experimental procedure. Several numerical simulations were performed for air-water flow, for the stratified and annular patterns. A resource of cut-off level, which depends of previous knowledge of the liquid fraction, was implemented in a way to improve the quality of the reconstructed images. The results obtained for several values of void fraction and for different patterns of flow, demonstrate the validity of the developed tomographic system.